A DISCIPLINE PENALTY ENFORCEMENT MODEL TOWARD NEUTRALITY VIOLATION OF GOVERNMENT EMPLOYEES ON REGIONAL ELECTION IN CENTRAL JAVA - Tedi Sudrajat; Sri Hartini (Faculty of Law, Universitas Jenderal Soedirman, 2015)
At this time, the implementation of neutrality for government employees are still use the legalistic approach. It doesn’t mean that this approach is problematic, but its not relevan when this approach is a self-implementing. That's why the policy is required by casuistry and situational approach, which means that the rule become the basis of law enforcement, while the case resolved by the consideration of the situation and the real reason that occur in the field. In this regard, the government should set standards, procedures and clear criteria against violations of neutrality as a basis for the imposition of penalties that are scalable and doesn’t have a double standard. Thats why its necessary to have institution that independent, objective and transparent. Keywords: Legal Policy, Neutrality, Law enforcement.